Indicadores morfofisiopatológicos em rebanhos ovinos da raça morada nova - Ferreira, Josiel Borges (Universidade Federal Rural do Semi-Árido, 2017)
The Morada Nova breed is widely distributed in the Northeast region of Brazil and represents a local patrimony of this region. However, the effective herds of the breed are diminished by factors related to the large replacement of these animals by specialized sheep for beef sheep, obstacles to breeding programs, and the economic and productive impacts caused by the diseases that affect the herds of the breed. Gastrointestinal parasites, mainly by nematodes, are one of the main problems in ruminant production systems. Its impact brings economic losses, which are associated with weight loss, reduced food consumption, decreased fertility rates and even animal mortality. Therefore, the objective of the present study was to evaluate the endoparasitic seasonality and performance measures in Morada Nova sheep, as well as to associate these variables to build an animal health index used for breed. Four herds were evaluated during the months of March, June, September and December, regarding their health and production characteristics, through parasitological measurements, blood tests and performance measures. The dissertation is composed of three chapters: (I) Theoretical reference, covering subjects related to the characterization of semiarid productive systems, the importance of animal genetic resources and resistance markers to endoparasites; (II) An evaluation of the parasitological, blood and performance measurements of Morada Nova breed over the months; (III) The construction of an index for sheep health. With this study, it was observed that the months of March and June presented higher risk factors for the health of Morada Nova breed sheep, created in a semiarid region, despite having a high adaptive degree , suffer from the high endoparasitary load, which is usually identified in this period. The construction of the Animal Health and Production Index (ISPA) will serve as a basis for other breeds and species and will provide useful information for the management of ruminant production systems
Keywords: Alterações hematológicas; morfofisiopatologia; método Famacha; pequenos ruminantes; região semiárida; Hematological disorders; pathophysiology; Famacha© method; small ruminants; semiarid region; CIENCIAS AGRARIAS::MEDICINA VETERINARIA